2003
DOI: 10.2136/sssaj2003.1428
|View full text |Cite
|
Sign up to set email alerts
|

In‐Season Nitrogen Status Sensing in Irrigated Cotton

Abstract: Nitrogen recommendations for Upland cotton (Gossypium hirsutum L.) in the western USA are based on spring soil NO−3–N tests. In‐season monitoring of plant N status is another approach. Our primary objective was to test spectral reflectance and chlorophyll meter measurements as in‐season N decision aids for irrigated cotton, and to compare these with soil test‐based N management. The secondary objective was to determine the fate of 15N as affected by N management and irrigation modes. Urea ammonium nitrate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 52 publications
4
30
0
Order By: Relevance
“…The recovery of 15 N fertilizer in plant ranged from 23 to 31% between the four fertigation schemes. Those values are within the range of plant 15 N recoveries previously reported for cotton (Freney et al 1993;Rochester et al 1993Rochester et al , 1997Torbert and Reeves 1994;Karlen et al 1996;Chua et al 2003). It is interesting to note that plant recovery was higher than the recovery of fertilizer N in soil in N-W treatment, but recovery of 15 N fertilizer in the soil was higher than plant recovery in other treatments.…”
Section: Recovery Of Fertilizer Nsupporting
confidence: 86%
“…The recovery of 15 N fertilizer in plant ranged from 23 to 31% between the four fertigation schemes. Those values are within the range of plant 15 N recoveries previously reported for cotton (Freney et al 1993;Rochester et al 1993Rochester et al , 1997Torbert and Reeves 1994;Karlen et al 1996;Chua et al 2003). It is interesting to note that plant recovery was higher than the recovery of fertilizer N in soil in N-W treatment, but recovery of 15 N fertilizer in the soil was higher than plant recovery in other treatments.…”
Section: Recovery Of Fertilizer Nsupporting
confidence: 86%
“…The total 15 N recovery under different treatments ranged from 46% to 66% with an average of 54%. These values were within the range of total recovery of 15 N in plants and soils reported by other studies for irrigated cotton (Freney et al, 1993;Rochester et al, 1994;Torbert and Reeves, 1994;Karlen et al, 1996), but were smaller than those reported by Chua et al (2003) and Fritschi et al (2004). The result showed that on average, more than 40% of the applied N was unaccounted from the soil-plant system during the growing season.…”
Section: N Recoverysupporting
confidence: 73%
“…Their results suggested that the impact of fertigation strategy on nitrate leaching was limited and nitrate leaching was not very significant under drip irrigation. Denitrification in soil wet zones therefore appears to be the highest possibility as a loss pathway (Thompson et al, 2000;Chua et al, 2003). This has been reported for irrigated cotton fields in Australia, where 43-63% loss of the applied N fertilizer was attributed mainly to denitrification (Freney et al, 1993;Chen et al, 1994).…”
Section: N Recoverymentioning
confidence: 74%
See 1 more Smart Citation
“…Scheer et al 2008b and identified denitrification as the main pathway of fertilizer losses from the soilplant system (Chua et al 2003;Hou et al 2007). For irrigated cotton only limited information is available on gaseous N emissions and denitrification losses.…”
Section: Introductionmentioning
confidence: 99%